Thermo-kinetic study to elucidate the bioenergy potential of Maple Leaf Waste (MLW) by pyrolysis, TGA and kinetic modelling - Ahmad, M.S. (Elsevier Ltd, 2021)
The present study aims to evaluate the feasibility of Maple Leaf Waste (MLW) for the first time to produce biofuel-bioenergy and chemicals. It is meaningful to understand the thermochemical conversion and degradation pattern of the MLW to evaluate its biofuel-bioenergy potential. Different degradation stages and zones based on temperature and mass loss were identified to understand the pyrolytic behaviour in depth. Four different heating rates were used to conduct kinetic and thermodynamic analysis. The pyrolysis temperature was concluded ranged from 200 Â°C to 430 Â°C at all heating rates to obtain maximum bioenergy products. The kinetic parameters of pyrolysis were obtained by analysing through iso-conversional models of Kissinger-Akahira-Sunose (KAS), Friedman and FlynnâWallâOzawa (FWO). The average values of activation energies (75â91 kJ molâ1), high heating values (16.32 MJ kgâ1), Gibb's free energies (261â269 kJ molâ1) and change in enthalpy (68â85 kJ molâ1) have shown the significant potential for bioenergy production and suitability of co-pyrolysis with other waste and biomass feedstock. Â© 2021 Elsevier Ltd